Yahoo Boys vs. Crypto Bros: Algorithmic amplification patterns of financial disinformation and fraud on X and Facebook - Nathan Oguche Emmanuel; Samuel Ameh (Informasi, 2025)
This paper examines how social media platforms X (Twitter) and Facebook algorithmically amplify financial disinformation and fraud, comparing two distinct archetypes: the relational deception of “Yahoo Boys” and the techno-utopian rhetoric of “Crypto Bros.” Using a mixed-methods approach—including algorithmic auditing, network analysis, and victim interviews—the research demonstrates that fraudulent content is amplified 67 times faster than legitimate content due to platform design that prioritizes high-arousal engagement. It reveals critical structural vulnerabilities in content moderation, including severe scale limitations and systemic biases that disproportionately fail non-English and African-language communities. The findings show that micro-targeting tools originally designed for advertisers are weaponized to prey on vulnerable users. The study concludes that platforms are active architects of digital financial risk, necessitating fundamental reforms in algorithmic design and moderation practices.